Removal of cadmium ions from aqueous solution using very small ionic liquids to water ratio without metal chelator and pH modifications - Abebe, Atakilt; Tilahun, Sossina; Mesfine, Mikias; Atlabachew, Minaleshewa (Ethiopian Journal of Science and Technology, 2025)
Solvent extraction is an energy-efficient technology which uses two immiscible phases. In this regard, solvents like hydrophobic 1-butyl-3-methylimidazolium hexafluorophosphate based ionic liquids have been used. The hydrophilicity of the metal ions is a challenge to use this method. Coordinating the metal ions by ligands, lowering the pH of the aqueous phase, modifying the ionic liquid itself in such a way that it can coordinate with the metal ions, employment of large ionic liquid to aqueous phase ratio (minimum of 1:1) were also the attempts made to improve the distribution coefficient of the ionic liquids. All these efforts are problematic in hindering the applications of ionic liquids in extraction. In this report, the extraction efficiencies of ionic liquids (C4mim][PF6], [C6mim][PF6] , [C8mim][PF6] and [C10mim][PF6]) from water samples containing Cd2+ using very small ionic liquid to water ratio (1:6 and 1:12) from a solution of concentrations 0.005 mg/L with out using any coordinating agent as an extractant and the need of changing the pH are disclosed. While ionic liquids to aqueous phase ratio 1:12 demonstrated extraction efficiencies of 75%, 83.75%, 87.50% and 100%, respectively; the 1:6 ratio extracted 87.50%, 100%, 100% and 100%, respectively which shows suitability of the later ratio for better extraction. Moreover, the recyclabilities of [C6mim][PF6] and [C8mim][PF6] was investigated and the result showed that they can be used at least for five cycles. A Linear calibration curve with good coefficient of determination was obtained during the analysis for determination of the metal in the extracts.